2015
DOI: 10.1021/bi501308k
|View full text |Cite
|
Sign up to set email alerts
|

Critical Determinants of Substrate Recognition by Cyclin-Dependent Kinase-like 5 (CDKL5)

Abstract: Cyclin-dependent kinase-like 5 (CDKL5) is a Ser/Thr protein kinase known to be associated with X-linked neurodevelopmental disorders. In a previous study, we identified amphiphysin 1 (Amph1) as a potential substrate for CDKL5 and identified a single phosphorylation site at Ser-293. In this study, we investigated the molecular mechanisms of substrate recognition by CDKL5 using Amph1 as a model substrate. Amph1 served as an efficient CDKL5 substrate, whereas Amph2, a structurally related homologue of Amph1, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…While the MH2 domain is highly conserved among all SMADs, the different structure of the MH1 domain of SMAD3, which does not contain the 30‐amino‐acid insert that is present in SMAD2 , could explain the specificity of the CDKL5‐dependent phosphorylation of SMAD3. Though recent observation has raised the possibility that the RPXSA motif might represent a consensus sequence for phosphorylation by CDKL5 , other studies have identified CDKL5 phosphorylation targets that do not contain this consensus motif , suggesting the presence of a different consensus sequence for CDKL5 phosphorylation or of a protein folding that creates a noncontiguous CDKL5 phosphorylation motif . SMAD3 seems to belong to this latter group because the MH1 domain does not present a RPXSA motif.…”
Section: Discussionmentioning
confidence: 96%
“…While the MH2 domain is highly conserved among all SMADs, the different structure of the MH1 domain of SMAD3, which does not contain the 30‐amino‐acid insert that is present in SMAD2 , could explain the specificity of the CDKL5‐dependent phosphorylation of SMAD3. Though recent observation has raised the possibility that the RPXSA motif might represent a consensus sequence for phosphorylation by CDKL5 , other studies have identified CDKL5 phosphorylation targets that do not contain this consensus motif , suggesting the presence of a different consensus sequence for CDKL5 phosphorylation or of a protein folding that creates a noncontiguous CDKL5 phosphorylation motif . SMAD3 seems to belong to this latter group because the MH1 domain does not present a RPXSA motif.…”
Section: Discussionmentioning
confidence: 96%
“…The former resembles the wellknown Plk1 kinase motif (52), whereas the latter is informative for proline-directed kinases (53). For B*07 ligands, the prevalent phosphorylation motif is (R/K)PXpS, which loosely confirms to the substrate motif of CDKL5 (54). Therefore, our data seem to predict that individuals expressing specific HLA allotypes may be more prone to present phosphorylated peptides following aberrant function of specific kinases, providing another reason for further research into personalized therapies.…”
Section: Phosphopeptidomics Of Hla-b Antigensmentioning
confidence: 56%
“…prompted the researchers to consider it a proline-directed protein kinase [21]. However, using Amph1 mutants and catalytic fragment of CDKL5, we were able to determine that CDKL5 recognises the RPXS (A/P) sequence [78]. Furthermore, Muñoz et al have confirmed that full-length CDKL5 also recognises this motif using peptide substrates [70].…”
Section: Neural Plasticitymentioning
confidence: 85%
“…These observations suggest that CDKL5 recognises not only the amino acid sequence in the vicinity of the phosphorylation site but also some other external structural elements of the proteins to which it binds. By conducting a detailed analysis of the recognition mechanism using Amph1 as a model substrate, we found that the catalytic fragment of CDKL5 recognises a characteristic structural element of Amph1 known as CLAP [78]. Ser/Thr kinases are known to phosphorylate both Ser and Thr, but we have shown that CDKL5 preferentially phosphorylates the Ser residue of the substrate [78].…”
Section: Neural Plasticitymentioning
confidence: 93%
See 1 more Smart Citation